PERAN ARSIPARIS DALAM PENGELOLAAN KEARSIPAN DI UIN RADEN INTAN LAMPUNG - Rosmaini, Yeni (UIN Raden Intan Lampung, 2020)
The improvement of an organization requires properly is to support the management can request data and information, one of them is the archive The purpose of this research is to improve orderly arrangement and management of archives in order to comply with the filing system in order to facilitate the searching back. Archival management activities can be running well when the supporting factors can be fulfilled from facilities and infrastructure, work mechanisms, and human resources of archival and funding managers. Because the archive is a source of organization memory and as a collective memory of the nation. The implementation of the archives in the UIN Raden Intan Lampung has not been fully yet in accordance with the expectations in Undang-Undang Nomor 43 Tahun 2009 (Law No. 43 of the year 2009), this is because the archival policy has not been implemented optimally by the organizers' Agencies. The method used in this research is a qualitative method with data collection techniques is observation and questioner.